Inauguration of the Rev. Benjamin B. Warfield, D.D., as professor of didactic and polemic theology - Warfield, Benjamin Breckinridge (Alumni collection, 1888)
The charge / by James T. Leftwich -- The idea of systematic theology considered as a science / by Benjamin B. Warfield.